2011
DOI: 10.2113/gssgfbull.182.6.507
|View full text |Cite
|
Sign up to set email alerts
|

The filament event near the Cenomanian-Turonian boundary in Tunisia: filament origin and environmental signification

Abstract: Abstract. -Near the Cenomanian-Turonian boundary, the filament event corresponds to the massive occurrence of thin elongate shells, probably bivalves which constitute, in the Bahloul Formation, about 40% of allochems. This biosedimentary event was described in several areas, such as in Tunisia, Algeria, Morocco, North America, Oman and Tibet. In Tunisia, filaments are well represented within well laminated black shales constituting the Bahloul Formation, late Cenomanian -early Turonian in age. These black shal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 19 publications
(35 reference statements)
2
9
0
1
Order By: Relevance
“…Four important bioevents that are commonly recognized within the latest Cenomanian-earliest Turonian transition (Keller et al, 2004;Coccioni and Luciani, 2004;Caron et al, 2006;Robaszynski et al, 2010;Negra et al, 2011;Kędzierski et al, 2012;Bomou et al, 2013;Denne et al, 2014;Lowery et al, 2014;Reolid et al, 2015) were identified within the section studied ( Fig. 2).…”
Section: Age Of the Xilitla Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four important bioevents that are commonly recognized within the latest Cenomanian-earliest Turonian transition (Keller et al, 2004;Coccioni and Luciani, 2004;Caron et al, 2006;Robaszynski et al, 2010;Negra et al, 2011;Kędzierski et al, 2012;Bomou et al, 2013;Denne et al, 2014;Lowery et al, 2014;Reolid et al, 2015) were identified within the section studied ( Fig. 2).…”
Section: Age Of the Xilitla Sectionmentioning
confidence: 99%
“…index ammonite Watinoceras (Caron et al, 2006;Negra et al, 2011). Building upon this consideration, we place the C-T boundary below bed 93 (at 15.8 m) in the studied section ( Fig.…”
Section: Age Of the Xilitla Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gale et al, 1993;Jenkyns et al, 1994Jenkyns et al, , 2017Tsikos et al, 2004;Scopelliti et al, 2006;Voigt et al, 2007;Gebhardt et al, 2010;Jarvis et al, 2011;Bomou et al, 2013;Dickson et al, 2017;Owens et al, 2017). Other observations associated with OAE 2 include an increase of siliceous plankton in the Umbria-Marche Basin during the event (Mort et al, 2007) or predating it in the Natih Basin (Van Buchem et al, 1996;Wohlwend et al, 2016), and blooms of pelagic bivalve filaments from the earliest Turonian across Northern Africa and Oman to Tibet (Negra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, algunos de los filamentos más gruesos presentan un ápice triangular y una estructura interna que consiste en capas o lamelas con diversas orientaciones (Figura 5D). En algunas capas estos filamentos se desprenden de fragmentos calcáreos de mayor tamaño (Figura 5E y F), lo cual es consistente con lo reportado por Scholle et al (1983), Scholle y Ulmer- Scholle (2003), Flügel (2004) y Negra et al (2011) para filamentos traslúcidos de origen metazoario (bivalvos); lo que descarta un origen microbiano para las formas con ápice de Xilitla.…”
Section: Situación Geográfica Y Marco Geológico-estratigráficounclassified